Clinical interpretation of cardiac troponin in athletes: From endurance exercise to exertional injury - John‐Henry L. Dean; Jeffrey C. Leggit; M. Alaric Franzos (PM&R, 2026)
Abstract Exertional heat illness (EHI) and exertional rhabdomyolysis (ER) are increasingly recognized causes of morbidity in competitive and tactical athletes. Cardiac troponin (cTn) elevation, traditionally viewed as a marker of myocardial necrosis, may also be seen in these settings and can create significant diagnostic and prognostic uncertainty. Although transient cTn elevation after endurance exercise is common and generally benign, extrapolation of this paradigm to exertional injury is likely problematic. This narrative review synthesizes current evidence regarding cTn elevation across three related but distinct contexts: isolated endurance exercise, ER, and EHI. We review the current understanding of cTn biology, emphasizing isoform‐specific differences between cTn I and T, assay‐related considerations, and mechanisms of cTn release beyond irreversible cardiomyocyte necrosis. In isolated endurance exercise, cTn elevation is typically transient, often normalizing over 24–72 hours, and has not been consistently associated with myocardial necrosis or adverse long‐term cardiovascular outcomes. In contrast, ER and EHI are different pathophysiologic states characterized by systemic metabolic stress, skeletal muscle injury, and in EHI, systemic hyperthermia and direct thermal injury. The prevalence and prognostic significance of cTn elevation in ER and EHI are poorly defined. Current data, largely extrapolated from nonexertional cohorts, suggest potential associations with increased morbidity and long‐term cardiovascular risk. However, prospective studies in ER and EHI are urgently needed to validate these findings. Accordingly, interpretation of cTn in exertional injury requires consideration of clinical context, troponin isoform and kinetics, electrocardiographic findings, and cardiac imaging. Improved understanding of these critical distinctions is essential to guide appropriate evaluation, risk stratification, and safe return‐to‐activity decisions.